Kemajuan Instansi Pendidikan: Bagaimana Peranan Meaningful Work dan Change-oriented ocb Pada Guru SMA? - Ramadan, Ananda Dwi; Sofiah, Diah; Prasetyo, Yanto (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
Abstract This study aims to determine whether there is a relationship between Meaningful Work and Change-oriented ocb in high school teachers in Gresik Regency. This analysis uses the dependent variable, namely Change-oriented ocb and the independent variable, namely Meaningful Work. This research is a type of quantitative research using correlational quantitative methods. The sampling technique in this study used a simple random sampling method where the subjects were taken from the entire population of 76 respondents. The subjects in this study were teachers at three X high schools in Gresik Regency and used instruments from Change-oriented ocb with Meaningful Work. The data analysis technique uses Spearman 'rho non-parametric correlation test analysis with the help of SPSS version 22.0 for Windows. The result of the correlation coefficient on the relationship between Meaningful Work and Change-oriented ocb is 0,311 with a significance level of 0,008 (p = <0.05) which indicates that the level of correlation coefficient on these variables has a positive relationship and very significant. This means that Change- Oriented OCB will increase along with the increase in Meaningful Work in High School Teachers. Keywords: (Change-oriented ocb, Education, Meaningful Work, Teacher). Abstrak Penelitian ini bertujuan untuk mengetahui apakah ada hubungan antara Meaningful Work dengan Change-oriented ocb pada Guru SMA di Kabupaten Gresik. Analisis ini menggunakan variabel dependen yaitu Change-oriented ocb dan variabel independen yaitu Meaningful Work. Penelitian ini merupakan jenis penelitian kuantitatif dengan menggunakan metode kuantitatif korelasional. Teknik pengambilan sampel pada penelitian ini menggunakan metode simple random sampling yang dimana subjek diambil dari kesuluruhan populasi sebanyak 76 responden. Subjek pada penelitian ini yaitu Guru pada tiga SMA X di Kabupaten Gresik dan menggunakan instrumen dari Change-oriented ocb dengan Meaningful Work. Teknik analisis data menggunakan analisis uji korelasi non parametric spearman’ rho dengan bantuan SPSS versi 22.0 for Windows. Hasil koefisien korelasi pada hubungan antara Meaningful Work dengan Change-oriented ocb sebesar 0,311 dengan taraf signifikansi sebesar 0,008 (p = <0,05) yang menunjukkan bahwa tingkat koefisien korelasi pada variabel tersebut memiliki hubungan positif yang sangat signifikan. Artinya Change-oriented ocb akan meningkat seiring dengan meningkatnya Meaningful Work pada Guru SMA. Kata Kunci: (Change-oriented ocb, Guru, Meaningful Work, Pendidikan)